Self-reported questionnaires for lymphoedema: a systematic review of measurement properties using COSMIN framework. (3rd April 2021) - Paramanandam, Vincent Singh; Lee, Mi-Joung; Kilbreath, Sharon L.; Dylke, Elizabeth S.
Abstract: Introduction: Lymphoedema may develop as a result of numerous genetic and traumatic causes; however, treatment for cancer is the most common cause of its development in more economically developed nations. This systematic review critically appraised, compared and summarised the measurement properties of lymphoedema-specific self-reported questionnaires (SRQs) measuring various patient-reported outcomes including quality of life (QOL), function, morbidity, and symptoms. Methods: Seven databases were searched to identify studies of the measurement properties of SRQs. Two review teams independently evaluated the quality of the individual studies using the risk of bias tool from the Consensus-based Standards for the Selection of Health Measurement Instruments (COSMIN). Measurement properties of the SRQs presented in the studies were then rated. Study level ratings were summarised for an SRQ if they were reported in multiple studies, and their overall quality of the evidence were then graded. Results: Forty articles, reporting on 19 SRQs were identified from 8615 records. The focus of the 19 SRQs included eight on QOL, four on symptoms, two on function, and two on impairment. The other three SRQs were on illness perception, self-efficacy, and patient-relevant treatment benefit, respectively. Eight and three SRQs were upper limb and lower limb-specific, respectively, whereas seven questionnaires were for both upper and lower limb lymphoedema. One SRQ was developed for head and neck lymphoedema. According to the COSMIN framework, none of the SRQs reviewed had sufficient evidence to support all nine measurement properties. In lower limb questionnaires, the LYMQOL-leg has sufficient content, structural, and construct validity as well as internal consistency and reliability. For upper limb lymphoedema questionnaires, the Lymph-ICF-UL had sufficient content and construct validity as well as reliability. Conclusion: LYMQOL-leg SRQ is recommended with confidence for evaluation of QOL of people with lower limb lymphoedema while the Lymph-ICF-UL is recommended for evaluation of the QOL of the breast cancer-related lymphoedema with some confidence. In view of the high level of the indeterminate ratings of the measurement properties of the existing SRQs, further research is desirable.